2007
DOI: 10.1177/0961203307081401
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of murine lupus disease in (NZB×NZW)F1 mice by sirolimus treatment

Abstract: Sirolimus is a new immunosuppressive drug used to avoid allograft rejection. The immunosuppressive effect of sirolimus is due to inhibition of the mammalian target of rapamycin, necessary for the proliferation and clonal expansion of activated T-cells. Because T-cells play a central role in the pathogenesis of autoimmune disease developed in (NZBxNZW)F1 mice, we evaluated the therapeutic use of sirolimus in such mice. (NZBxNZW)F1 female mice received 1mg/kg/day of sirolimus from 12 to 37 weeks of age. The deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
4
22
0
1
Order By: Relevance
“…By studying the models of lupus mice (NZB Â NZW F1 lupus mice and female MLR/lpr lupus mouse), it was found that rapamycin can effectively reduce the production of autoantibody, decrease vascular immune complex deposition and proteinuria, significantly prolong the survival [32,33]. In clinical terms, rapamycin not only suppresses the SLE activity, also reduces the dose corticosteroids [34].…”
Section: Mtor Signaling Pathwaymentioning
confidence: 99%
“…By studying the models of lupus mice (NZB Â NZW F1 lupus mice and female MLR/lpr lupus mouse), it was found that rapamycin can effectively reduce the production of autoantibody, decrease vascular immune complex deposition and proteinuria, significantly prolong the survival [32,33]. In clinical terms, rapamycin not only suppresses the SLE activity, also reduces the dose corticosteroids [34].…”
Section: Mtor Signaling Pathwaymentioning
confidence: 99%
“…Rapamycin has shown great potency in blocking the development of SLE in the MRL/lpr 5 and NZB/W F1 animal models 41,175 , in which autoimmunity, T-cell hyper-reactivity, titres of ANA and anti-DNA antibodies, glomerular immunoglobulin deposition, proteinuria, nephritis, and overall survival were all improved. Importantly, rapamycin also attenuates the severity of established nephritis 176 .…”
Section: Mtor As a Therapeutic Target In Rheumatic Diseasementioning
confidence: 99%
“…Rapamycin has been used as an immunosuppressive agent and several reports have shown that rapamycin decreased the development of glomerulonephritis in NZB/W and MRL/lpr mice. [70][71][72][73] Although inhibition of mTOR has been shown to exert beneficial effects in lupus mice, other reports have suggested a negative outcome with the use of rapamycin in regulating anti-GBM glomerulonephritis, depending on timing of administration. 74 mTOR blockage by rapamycin has also been shown to induce proteinuria and renal deterioration and induce focal segmental glomerulonephritis.…”
Section: Egcg Inhibits Inflammation In Lupus Mesangial Cells a Peairsmentioning
confidence: 99%